Assessing the Impact of COVID-19 on Corporate Investment Behavior - Umar Farooq; Mosab I. Tabash; Suhaib Anagreh; Mohammed Alnahhal (Emerging Science Journal, 2021)
The current wave of COVID-19 outbreak has created new strategical challenges for policy officials of the industrial sector across the world. The effect of COVID-19 is more in developing economies where industrial sector is already struggling for its stability. This study introduces the impact of COVID-19 on the corporate investment behavior of non-financial publicly listed firms of Pakistan. To achieve the objective, we employ the panel data ranging from 2010 to 2020 and apply the difference-in-differences (DID) model to quantifies the empirical relationship. The outcomes of DID model suggest that the pandemic period and treatment have a significant and negative impact on corporate capital investment behavior. During pandemic spread period, the enterprises have limited their investment into fixed assets due to less productive use of such assets. Similarly, industries that exist in high-impact areas face a negative investment growth rate due to quarantine policy, fewer social movements, and high installing cost of new machinery. However, this negative effect diminishes across those firms that have a quick cash inflow rate and more availability of bank loans. These two factors serve as a financial setback against the adversities of pandemic. By drawing upon the empirical reasoning on the effect of COVID-19, this study also presents possible solutions to alienate unfavorable impacts of this pandemic. Current analysis can be considered as an early attempt towards investigating the consequences of COVID-19 on investment decisions of industrial sector.JEL Classification: G32: G31: G40: C33 Doi: 10.28991/esj-2021-SPER-11 Full Text: PDF